1984
DOI: 10.1111/j.1751-1097.1984.tb03419.x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Addition of Amino Acids and Peptides to Polyuridylic Acid

Abstract: The quantum yields for photochemical addition of glycine and the L-amino acids commonly occurring in proteins (excluding proline) to polyuridylic acid have been determined in deoxygenated phosphate buffer at pH 7, using a tluorescamine assay technique. All twenty amino acids were found to be reactive. with cysteine. tryptophan, phenylalanine, tyrosine, arginine, lysine and methionine being the most reactive. The analogous quantum yields for a series of eighteen dipeptides of the form glycyl X (X being one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…The potential complexity of irradiated DNA-protein systems is a major challenge to investigators who try to identify the amino acid and nucleobase partners in UV-induced DNA-protein cross-links. Shetlar and coworkers (26)(27)(28) measured the apparent quantum yields for 19 amino acids and selected di-and tripeptides toward photoaddition to DNA and homopolynucleotides of the major DNA and RNA bases. None of the amino acids, when incorporated into a glycyl dipeptide, can be regarded as unreactive in photoaddition to the macromolecules studied in the survey.…”
Section: Introductionmentioning
confidence: 99%
“…The potential complexity of irradiated DNA-protein systems is a major challenge to investigators who try to identify the amino acid and nucleobase partners in UV-induced DNA-protein cross-links. Shetlar and coworkers (26)(27)(28) measured the apparent quantum yields for 19 amino acids and selected di-and tripeptides toward photoaddition to DNA and homopolynucleotides of the major DNA and RNA bases. None of the amino acids, when incorporated into a glycyl dipeptide, can be regarded as unreactive in photoaddition to the macromolecules studied in the survey.…”
Section: Introductionmentioning
confidence: 99%
“…(t .-seryl-L-prolyl-L-seryl-L-tyrosyl-L-seryl-L-prolyl-L-threonine). From the standpoint of experimental design, the important aspect of this selection is that it contains a tyrosine, which has been shown in a number of studies (see below) to participate in reactions with nucleobases and which has been shown in survey studies to be reactive with DNA itself (4) and with homopolynucleotides of each of the nucleobases contained in DNA and RNA (5,6). A second reason for our choice of peptide is that it likely has biological importance, as it is present as a repeating heptad sequence in the Cl-terminal domain of the largest subunit of RNA polymerase I1 (RNA pol 11) utilized in eukaryotic cells for transcription of DNA to mEWA.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, all nucleic acids and all 20 amino acids can form crosslinks; however, there are great differences in their reactivity. Crosslinking studies of single amino acids to DNA showed that cysteine, lysine, phenylalanine, tryptophan, and tyrosine are the most reactive, while alanine, aspartic and glutamic acids, serine and threonine are rather unreactive [57]. As the excited nucleotides can only react with amino acids in close spatial proximity, the native structure of the protein-RNA complex remains relatively undisturbed and the crosslinks formed fix contacts that are present in the native complex.…”
mentioning
confidence: 96%